Epidemiology, treatments, and related biomarkers of locally advanced or metastatic urothelial carcinoma in Chinese population: A scoping review - Wang He; Changhao Chen; Tianxin Lin; Qian Xu; Chong Ye; Jieyi Du; Jian Huang (Cancer Medicine, 2023)
Abstract Objective Bladder cancer is the 13th most common cancer in China with the predominant histologic type being urothelial carcinoma (UC). Locally advanced and metastatic (la/m) UC accounts for 12% of UC and the five‐year survival rate is only 39.4%, imposing a significant disease and economic burden on the patients. The aim of this scoping review is to synthesize existing evidence of epidemiology, the landscape of treatment options and associated efficacy and safety profiles, as well as treatment‐related biomarkers among Chinese la/mUC patients. Methods A systematic search was conducted on five databases (PubMed, Web of Science, Embase, Wanfang, and CNKI) from January 2011 to March 2022 based on the scoping review criteria in accordance with the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis Extension for Scoping Reviews. Results A total of 6211 records were identified, and further review resulted in 41 relevant studies that met all criteria. Additional searches were conducted on epidemiology and treatment‐related biomarkers of bladder cancer to supplement the evidence. Among 41 studies, 24 reported on platinum‐based chemotherapy, eight on non‐platinum‐based chemotherapy, six on immunotherapy, two on targeted therapy, and one on surgery. Efficacy outcomes were summarized by line of therapy. Treatment‐related biomarkers including PD‐L1, HER2, and FGFR3 alterations were identified, and the alteration rate of FGFR3 of Chinese UC patients was lower than that of the western patients. Conclusions Despite chemotherapy has been the main treatment choice for decades, appealing new therapeutic strategies including ICIs, targeted therapies and ADCs were applied in clinical practice. Further research on epidemiology and treatment‐related biomarkers of la/mUC patients is needed given only a limited number of studies have been identified thus far. High genomic heterogeneity and complexity of molecular features were observed among la/mUC patients; thus, further studies are required to identify critical drivers and promote potential precise therapies.